More homogeneous capillary flow and oxygenation in deeper cortical layers correlate with increased oxygen extraction - Baoqiang Li; Tatiana V Esipova; Ikbal Sencan; Kıvılcım Kılıç; Buyin Fu; Michele Desjardins; Mohammad Moeini; Sreekanth Kura; Mohammad A Yaseen; Frederic Lesage; Leif Østergaard; Anna Devor; et al. (eLife, 2019)
Our understanding of how capillary blood flow and oxygen distribute across cortical layers to meet the local metabolic demand is incomplete. We addressed this question by using two-photon imaging of resting-state microvascular oxygen partial pressure (PO2) and flow in the whisker barrel cortex in awake mice. Our measurements in layers I-V show that the capillary red-blood-cell flux and oxygenation heterogeneity, and the intracapillary resistance to oxygen delivery, all decrease with depth, reaching a minimum around layer IV, while the depth-dependent oxygen extraction fraction is increased in layer IV, where oxygen demand is presumably the highest. Our findings suggest that more homogeneous distribution of the physiological observables relevant to oxygen transport to tissue is an important part of the microvascular network adaptation to local brain metabolism. These results will inform the biophysical models of layer-specific cerebral oxygen delivery and consumption and improve our understanding of the diseases that affect cerebral microcirculation.